The role of adhesive molecules in endometrial cancer: part II - Wojciechowski, Michał; Krawczyk, Tomasz; Śmigielski, Janusz; Malinowski, Andrzej (Menopause Review/Przegląd Menopauzalny, 2010)
The carcinogenesis is a result of both functional and structural disorders in the tissue. It initiates as a mutation in a gene encoding protein that is essential for cellular function. The subsequent cascade of events leads to accumulation of mutations and loss of cellular function. The cell loses its tissue-specific morphology, disconnects from other cells and extracellular matrix and migrates – the invasion begins. It is now clear that adhesive molecules are a key player in this cascade. These proteins of the cell membrane surface are responsible for attachment of the cells to each other and to the extracellular matrix. These interactions are crucial for both structural and functional tissue organization. Lack of this homeostasis destroys the tissue architecture and impairs its function and results in invasion. Abnormal expression of adhesive molecules was reported in all examined cancers, including endometrial cancer. Endometrial cancer is the most common gynaecological cancer in developed countries. Although in many cases diagnosed and treated in early stages, and thus with good results, some patients cannot be cured. Complete knowledge of the pathogenesis of the disease will be helpful in identifying the patients with negative prognostic factors, increased risk of recurrence and, perhaps, to find other therapeutic options. In the paper we are trying to sum up the up-to-date knowledge of the role of adhesive molecules in pathogenesis of endometrial cancer.